Hubungan Kepatuhan Tim Bedah dalam Penerapan Surgery Safety Checklist dengan Infeksi Luka Operasi dan Lama Rawat Inap pada Pasien Seksio Sesarea di Rumah Sakit Umum Daerah Kabupaten Barru - Amiruddin Amiruddin; Ova Emilia; Shinta Prawitasari; Leo Prawirodihardjo (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2018)
Background: Surgical Patient Safety is essential to be carried out in operating theatre to prevent mortality and surgical complication. Patient safety is the basic principal in medical care and a major component of medical care management in hospital (WHO, 2009).Objective: To investigate association between SSC implementation among surgical team, surgical site infection and duration of hospital stay.Method: This is an analytical cross sectional study. Population of this study was women who underwent cesarean section with live birth in Barru general hospital during 1 December 2016-30 April 2017. This study was carried out in Barru general hospital, 137 samples met inclusion and exclusion criteria. Data was obtained from medical records. Maternal outcome were duration of hospital stay, surgical site infection, and maternal mortality. Besides, this study also assesed knowledge and compliance of surgical team in implementation of SSC. The result of this study was analysed with computer statisctics analysis program.Result adn Discussion: One-hundred thirty seven patients met study criteria. Compliance of surgery team in SSC was 64%,. SSC was not implemented precisely in 36% patients (49 patients). There is no significant association between surgical team compliance with surgical site infection in cesarean section patients (p=0.078). A significant association was found between surgical team compliance with duration of hospital stay (p=0.006).Conclusion: The surgical team compliance in implementation of SSC was not yet optimal. An intensive socialization is needed to improve compliance of team in order that SSC implementation run promptly. This was part of efforts to reduce post operative complication and shorten hospital stay.Keywords: SSC, cesarean section, compliance, infection, duration of hospital stay